Problems in Speaking Skills: How is EFL Students' Perception? - Harahap, Alya (Institut Agama ISlam Negeri Palangka Raya, 2022)
AbstractOne of the important aspects that must be learned by humans is language. Language itself is used to make it easier for us to interact with each other and exchange information in communication. The purpose of this research is to analyze the problems experienced by EFL learners in speaking English at TBI class B batch 2020 at IAIN Palangka Raya. The research method used in qualitative research. In collecting the results, the researcher used a questionnaire about speaking problems in learning a foreign language which took the theory of Penny Tang (1997). The data in this study were taken from 15 students in a TBI semester 5 class. The result of the study is that data shows that around 46.7% of students often use their mother tongue in English classes. Full use of English but only about 6% and the few remaining students sometimes combine used of English and their mother tongue. Then, a percentage of respondents around 66.7% agreed that English is harder than the mother tongue.